2008
DOI: 10.1136/gut.2008.155812
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of treatment with infliximab in 614 patients with Crohn's disease: results from a single-centre cohort

Abstract: Background and aims: This observational study assessed the long-term clinical benefit of infliximab (IFX) in 614 consecutive patients with Crohn's disease (CD) from a single centre during a median follow-up of 55 months (interquartile range (IQR) 27-83). Methods: The primary analysis looked at the proportion of patients with initial response to IFX who had sustained clinical benefit at the end of follow-up. The long-term effects of IFX on the course of CD as reflected by the rate of surgery and hospitalisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

28
395
8
18

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 495 publications
(453 citation statements)
references
References 21 publications
28
395
8
18
Order By: Relevance
“…The medical records of 492 unselected patients (or 464 with outcome data, used here as the denominator to calculate rates) treated with infliximab at the Mayo Clinic (1998-2002) were systematically reviewed. The study showed an 86 % initial response rate (or 80 % calculated on an ITT basis), similar to the 82-89 % reported in most other publications such as the pediatric REACH trial [5], the Edmonton cohort [6], the large Leuven cohort [7], the Leeds cohort [8], and the Targan initial RCT [1] but higher than the short-term response rate achieved in the ACCENT trial (65 %) [2]. This figure (82-89 %) also includes those with partial response, variably defined in the different studies.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The medical records of 492 unselected patients (or 464 with outcome data, used here as the denominator to calculate rates) treated with infliximab at the Mayo Clinic (1998-2002) were systematically reviewed. The study showed an 86 % initial response rate (or 80 % calculated on an ITT basis), similar to the 82-89 % reported in most other publications such as the pediatric REACH trial [5], the Edmonton cohort [6], the large Leuven cohort [7], the Leeds cohort [8], and the Targan initial RCT [1] but higher than the short-term response rate achieved in the ACCENT trial (65 %) [2]. This figure (82-89 %) also includes those with partial response, variably defined in the different studies.…”
supporting
confidence: 85%
“…1b). A total of 43 % of those with outcome data in the current report of Seminerio et al required at least one surgery at some time during the follow-up period after starting infliximab as compared with 24 % in the Leuven cohort [7]. Most other reports did not report on surgery rate leaving open the question of whether infliximab alters the natural history of the disease.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Approximately 10 % of patients with " refractory " or newly diagnosed Crohn ' s disease seem not to respond to anti-TNF treatment ( 7,8 ). Th e mechanism of this lack of effi cacy is unclear.…”
mentioning
confidence: 99%
“…A recent report on the outcome of prolonged infl iximab therapy in patients with Crohn ' s disease revealed that aft er a median follow-up time of 55 months, 63 % of patients had sustained benefi t and 22 % experienced loss of response despite increases in dose and shortening of dosing intervals. Th e annual dropout rates averaged 11 % on episodic and 7 % on scheduled maintenance therapy ( 8 ).…”
mentioning
confidence: 99%